Freqüência de parasitas intestinais em felinos mantidos em zoológicos Frequency of intestinal parasites in felines kept in zoos - G.C.K. Müller (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2005)
The endoparasites occurrence in felines confined in two Zoos, between December 1999 and April 2000, was studied. Fecal samples of 18 felines (Panthera tigris, Panthera leo, Felis serval, Panthera onca, Puma concolor, Leopardus tigrinus and Leopardus wiedii) were collected and the methods of Faust, modified Baermann and Hoffmann, were used for fecal analyses. Three genera were identified in the feces: Trichuris spp., Toxocara spp. and Giardia spp. In the zoo of Pomerode, six animals (46%) were infected by Trichuris spp. and/or Giardia spp. and all samples from the zoo of Brusque were infected by Trichuris spp., Toxocara spp. and Giardia spp.